2013
DOI: 10.1111/jpi.12086
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐enhanced autophagy protects against neural apoptosis via a mitochondrial pathway in early brain injury following a subarachnoid hemorrhage

Abstract: Melatonin is a strong antioxidant that has beneficial effects against early brain injury (EBI) following a subarachnoid hemorrhage (SAH) in rats; protection includes reduced mortality and brain water content. The molecular mechanisms underlying these clinical effects in the SAH model, however, have not been clearly identified. This study was undertaken to determine the influence of melatonin on neural apoptosis and the potential mechanism of these effects in EBI following SAH using the filament perforation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
114
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 43 publications
9
114
2
Order By: Relevance
“…The endovascular perforation SAH rat model was produced as previously described with modifications [24]. Briefly, after the rats were anesthetized with an intraperitoneal injection of pentobarbital (40 mg/kg), the left carotid artery and its branches were exposed.…”
Section: Sah Rat Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The endovascular perforation SAH rat model was produced as previously described with modifications [24]. Briefly, after the rats were anesthetized with an intraperitoneal injection of pentobarbital (40 mg/kg), the left carotid artery and its branches were exposed.…”
Section: Sah Rat Modelmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [24]. The cytoplasmic and nuclear protein extracts were prepared with the NE-PER nuclear and cytoplasmic extraction reagents (Thermo, Rockford, IL, USA) according to the manufacturer's instructions.…”
Section: Western Blotmentioning
confidence: 99%
“…Melatonin treatment also inhibits the rotenone-induced impaired neuromuscular coordination, neuronal death, and DNA damage [81,82]. It attenuates apoptosis and oxidative stress in neurons and mesenchymal stem cells by upregulating the antiapoptotic protein bcl-2 [83,84]. It also alters the cell death processes in response to age-related oxidative stress and apoptosis in the brain of senescenceaccelerated mice [85].…”
Section: Melatonin As Antiapoptotic Moleculementioning
confidence: 99%
“…Recent studies have showed the antiapoptotic property of melatonin in rodent brain and in cell culture studies. Melatonin attenuates the neuron apoptosis in hippocampus and oxidative stress during chronic intermittent hypoxia [83]. It inhibits the β-amyloid generation and cholinergic dysfunction in the hippocampus of aged rats by its antiapoptotic effects [95].…”
Section: Melatonin As Antiapoptotic Moleculementioning
confidence: 99%
“…Western blot analysis was performed as previously described [7]. Briefly, the left basal cortical sample was homogenized and centrifuged at 1000 g for 10 min at 4°C.…”
Section: Western Blotmentioning
confidence: 99%